Performance of Geopolymer Concrete in Aggressive Environment - Mohd Salleh, Muhammad Farid (IRC, 2016)
The consumption of cement had caused pollution to the atmosphere. The cement industry is responsible for significant CO2 emissions because of its production. The carbon dioxide gas production is based from the process of burning large quantities of fuel and inherent to the basic process of calcinations of limestone. The process of making Portland Cement basically produce a large amount of CO2 emissions and other greenhouse gases.